The Semantic Associative Ability in Preschoolers with Different Language Onset Time - Di Giacomo, Dina; Ranieri, Jessica; Donatucci, Eliana; Caputi, Nicoletta; Passafiume, Domenico (Frontiers in Psychology, 2016)
Aim of the study is to verify the semantic associative abilities in children with different language onset times: early, typical, and delayed talkers. The study was conducted on the sample of 74 preschool children who performed a Perceptual Associative Task, in order to evaluate the ability to link concepts by four associative strategies (function, part/whole, contiguity, and superordinate strategies). The results evidenced that the children with delayed language onset performed significantly better than the children with early language production. No difference was found between typical and delayed language groups. Our results showed that the children with early language onset presented weakness in the flexibility of elaboration of the concepts. The typical and delayed language onset groups overlapped performance in the associative abilities. The time of language onset appeared to be a predictive factor in the use of semantic associative strategies; the early talkers might present a slow pattern of conceptual processing, whereas the typical and late talkers may have protective factors.